2010
DOI: 10.1007/s00198-010-1219-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural parameters of normal and osteoporotic human trabecular bone are affected differently by microCT image resolution

Abstract: The results suggest that structural differences between osteoporotic and normal trabecular bone may not be reliably detected with clinical CT scanners providing image voxel sizes above 100 µm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 37 publications
(58 reference statements)
1
46
0
Order By: Relevance
“…Variances among different studies are probably due to a combination of differences in skeletal sites, sample preparation, ultrasound measurement methodology, microCT hardware and microarchitectural feature estimation algorithm. A recent report addresses the effect of microCT image resolution (Isaksson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variances among different studies are probably due to a combination of differences in skeletal sites, sample preparation, ultrasound measurement methodology, microCT hardware and microarchitectural feature estimation algorithm. A recent report addresses the effect of microCT image resolution (Isaksson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…After ultrasound and DXA measurements had been performed, cancellous bone specimens were cut down to dimensions approximately 2.0 cm  4.0 cm  1.8 cm and imaged at an isotropic voxel size of 17.2 lm (nominal resolution). This resolution has been reported to be sufficient to reveal significant differences between normal and osteoporotic human trabecular bone for bone volume fraction (BV/TV), trabecular thickness (Tb.Th), degree of anisotropy (DA), trabecular number (Tb.N), trabecular spacing (Tb.Sp), and structural model index (SMI) (Isaksson et al, 2011). Within the 2.0 cm  4.0 cm  1.8 cm reconstruction volume, an interior volume, approximately 1.8 cm  3.6 cm  1.6 cm (similar to the DXA analysis volume) was delineated for micro-structural analysis.…”
Section: Microctmentioning
confidence: 99%
“…A previous study demonstrated that it is the resolution of raw data that primarily determines the accuracy of models as the bone volume fraction of bone volume/total volume was predominantly affected by the scanning resolution (22). The scanning resolution of the µ-CT system used in our study was 33.355 µm, which was enough to depict the microarchitecture of human trabecular bone (23,24). In another study, the recommended resolution in finite element models of trabecular bone was one quarter of trabecular thickness (25).…”
Section: Discussionmentioning
confidence: 87%
“…Macroscopic 3D bone geometry and inhomogeneities in bone mineral density (BMD) and mechanical properties can be assessed with quantitative CT (QCT) [50,51]. Unfortunately, the resolution of clinical CT equipment is insuffi cient to resolve trabecular architecture [52]. However, clinicallevel CT data can be used to measure the structural anisotropy for improved mechanical characterization of trabecular bone [53].…”
Section: Discussionmentioning
confidence: 99%